Alkaline Autoclave Leaching of Refractory Uranium-Thorium Minerals - S A. Milani; A Sam (مجله علوم و فنون هسته‌ای, 2011)
This paper deals a with the study of an innovative method for processing the Oman placer ores by alkaline leaching in ball mill autoclaves, where grinding and leaching of the refractory minerals take place simultaneously. This was followed by the selective separation of thorium and uranium from lanthanides by autoclave leaching of the hydroxide cake with ammonium carbonate-bicarbonate solutions. The introduced method is based on the fact that thorium and uranium form soluble carbonate complexes with ammonium carbonate, while lanthanides form sparingly soluble double carbonates. It was found that a complete alkaline leaching of Oman placer ores (98.0%) was attained at 150 and 175°C within 2.5 and 2h, respectively. Oman placer ores leaching was intensified and accelerated in a ball mill autoclaves as a result of the grinding action of steel balls, removal of the hydroxide layer covering ores grains and the continuous contact of fresh ore grains with alkaline solution. The study of selective carbonate processing of hydroxide cake with ammonium carbonate-bicarbonate solutions on autoclave under pressure revealed that the complete thorium recovery (97.5%) with uranium recovery (90.8%) and their separation from the lanthanides were attained at 70-80°C during 1-2h. The extraction of  lanthanides in carbonate solution was low and did not exceed 4.6%.